Degradation : what the history of obscenity tells us about hate speech - Saunders, Kevin Wall, 1947- (New York : New York University Press, 2016)
Throughout history obscenity has not really been about sex but about degradation. In this study of the relationship between obscenity and hate speech, First Amendment specialist Kevin W. Saunders traces the legal trajectory of degradation as it moved from sexual depiction to hateful speech.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Hate speech; Obscenity (Law); Pornography; Hate speech -- United States; True Crime; United States of America, USA; Social services & welfare, criminology; Jurisprudence & general issues; Criminal law: procedure & offences